STRATEGIC METHODOLOGY FOR TEACHING ONOMASTIC UNITS IN ENGLISH AND UZBEK LANGUAGES BASED ON A LINGUOCULTUROLOGICAL APPROACH - Mamatkulova Bakhtijon Ravshanovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines strategic methodology for teaching onomastic units in English and Uzbek languages through a linguoculturological approach. The study highlights the importance of proper names (anthroponyms, toponyms, ethnonyms) as carriers of cultural and historical information. A strategic integration of linguistic and cultural components is proposed to enhance learners’ communicative and intercultural competence. The research emphasizes modern pedagogical strategies such as contextual learning, comparative analysis, and culturally oriented tasks. The findings suggest that a strategic approach to teaching onomastics fosters deeper understanding of national identity, cultural values, and language usage in real communicative contexts.